Analisis Prinsip Syariah Pada Pembiayaan Modal Usaha: Studi Kasus BMT Mandiri Sejahtera Kecamatan Sugio Kabupaten Lamongan - Febrianti Nilam Sari; Clarashinta Canggih (CV ODIS, 2021)
The purpose of this study is to determine the conformity of Sharia principles in business capital financing at BMT Mandiri Sejahtera, Sugio sub-district branch. The method was descriptive qualitative with data collection techniques through interviews and documentation. The validity test used the source triangulation technique. This study indicates that BMT Mandiri Sejahtera has three Sharia contracts in business capital financing. It consists of Rahn, murabahah and mudharabah. Rahn is the most popular financing contract. There have been violations of shariah rules on Rahn in 2019, whereas, for murabahah and mudharabah financing contracts, they have followed the existing Sharia rules. Keywords: Baaitul maal tamwil, financing, Sharia contract, rahn, murabahah, mudharobah